Leak detection and location in liquid pipelines by analyzing the first transient pressure wave with unsteady friction. (July 2019) - Diao, Xu; Shen, Guodong; Jiang, Juncheng; Chen, Qiang; Wang, Zhirong; Ni, Lei; Mebarki, Ahmed; Dou, Zhan
Abstract: Leakages in pipelines can cause serious consequences, such as economic loss, or fire and explosion. Hence, leak detection and location techniques are of crucial importance for pipeline maintenance, safety of industry facilities and environment. A modified transient-based method is proposed in this paper for leak detection and location in a reservoir-pipe-valve (RPV) system. The leak location model is based on the time when a pressure wave propagates from the valve to the leak location and back again. Furthermore, in the leak detection model, the one-dimensional unsteady friction model is introduced into Method of Characteristics (MOC). Then, the governing equations are derived as a ternary system of equations, in which the unknown parameters, especially leak size coefficient, are obtained by analyzing the first transient pressure wave. To validate the method efficiency, both one leak and two leaks situations are taken into consideration in simulation. The simulated results show notable correlations between the model and real leak locations. Additionally, the errors between calculated and actual values of the parameters remain in acceptable ranges. Finally, the developed method is verified by experimental data, and the results demonstrate that it has high accuracy and shows a great performance in leak detection and location. Highlights: Only investigating the first peak of transient pressure wave. A ternary system of equations are derived for leak detection based on unsteady friction model. Both one leak and two leaks situations are conducted.